Hyperon-meson and delta-meson coupling to protoneutron stars structure using the nonlinear Walecka model. (July 2015) - Souto, W A; Oliveira, J C T; Rodrigues, H; Duarte, S B; Chiapparini, M
Abstract: In this work we determine the equation of state and the population of baryons and leptons and discuss the effects of the hyperon-meson coupling constants to the formation of delta resonances in the stellar medium. We also discuss the structure of the protoneutron stars including the delta matter in their composition, and compared the results of a cooled neutron star, after escape of neutrinos. For protoneutron stars structure and composition, the neutrinos are considered trapped.